Tourist Potential in a Sustainable Approach. An Application Case - Eddy Soria-Leyva (Anuario Facultad de Ciencias Económicas y Empresariales, 2015)
In this research is proposed a methodology to evaluate the tourist potential with a sustainable approach and it is validated through an application in the municipality of the Tercer Frente, Santiago de Cuba. With this aim, some instruments of measure and mathematical formulas are submitted in order to obtain discriminating information about tourist resources, taking into account the delimitation of zones for the tourist development and the classification of determining factors of the tourist potential according to the capability of attraction and reception of the tourist demand, becoming adapted to the historic concrete conditions of the territory. Therefore, its application will determine a solid base for the future planning of tourist local development of this municipality. Among the main conclusions, it is deduced that Tercer Frente is a secondary semi-specialized destination which has medium tourist potential and possibilities to increase the spatial correlation among the tourist plant and the distribution of attractions in five zones.